A More Viscous‐Like Solar Wind Interaction With All the Giant Planets. Issue 15 (11th August 2018) - Masters, A.
Abstract: Identifying and quantifying the different drivers of energy flow through a planetary magnetosphere is crucial for understanding how each planetary system works. The magnetosphere of our own planet is primarily driven externally by the solar wind through global magnetic reconnection, while a viscous‐like interaction with the solar wind involving growth of the Kelvin‐Helmholtz (K‐H) instability is a secondary effect. Here we consider the solar wind‐magnetosphere interaction at all magnetized planets, exploring the implications of diverse solar wind conditions. We show that with increasing distance from the Sun the electric fields arising from reconnection at the magnetopause boundary of a planetary magnetosphere become weaker, whereas the boundaries become increasingly K‐H unstable. Our results support the possibility of a predominantly viscous‐like interaction between the solar wind and every one of the giant planet magnetospheres, as proposed by previous authors and in contrast with the solar wind‐magnetosphere interaction at Earth. Plain Language Summary: Understanding how energy flows from the Sun to the planets is a complex problem with many different aspects. One of the ways in which energy is transferred is via the continuous flow of charged particles away from the Sun known as the solar wind. When this solar wind encounters the invisible magnetic bubble (magnetosphere) that surrounds each of the magnetized planets (e.g., the Earth), it is generally forced to flow around the obstacle. However, there are important processes that can break down this natural magnetic shielding and allow energy to enter near‐planet space. This study compares two different and important ways in which the breakdown can take place. We show that the dominant mechanism in the context of Earth's magnetosphere may be less important at planets farther from the Sun, whereas a mechanism more like viscous drag may grow to dominate at the giant planets in the outer solar system. This would be in contrast to conventional understanding and is highly relevant for an emerging and ongoing debate that concerns scientists working on all planetary magnetospheres, both those known to exist in our solar system and those that are likely present around other stars. Key Points: Evolving solar wind conditions with distance from the Sun controls the nature of each solar wind‐magnetosphere interaction Reconnection electric fields at magnetopauses get weaker while boundaries become more Kelvin‐Helmholtz unstable with distance from the Sun The solar wind‐magnetosphere interaction at each of the giant planets is more viscous‐like than it is at Earth